Tumor-infiltrating nerves: unraveling the role of cancer neuroscience in tumorigenesis, disease progression, and emerging therapies - Xixi Wang; Yifei Fan; Qin Wang; Xiaojun Shu; Junyi Lin; Juqing Guo; Zhi Li; Jun Xu (Discover Oncology)
Abstract Cancer neuroscience has evolved as a novel discipline that elucidates the intricate relationships between the neurological system and neoplasms. Research indicates that the ablation of particular nerve types, including parasympathetic, sympathetic, or sensory nerves, can suppress tumour growth in a tissue-specific manner. Moreover, numerous tumours exhibit greater innervation density than their normal tissue equivalents, prompting essential enquiries on the processes of tumour innervation and its molecular contribution to disease progression. These findings underscore the significant clinical ramifications of tumour axon production and establish a theoretical foundation for the development of anticancer treatments aimed at neural mechanisms. Current studies have investigated the potential effectiveness of repurposing neuroactive pharmaceuticals as anticancer medicines, and emerging therapies for chemotherapy-induced peripheral neuropathy. This review seeks to encapsulate the function of tumor-infiltrating nerves in carcinogenesis and disease advancement, while also examining novel therapeutic approaches in this domain.